ANALYTICAL RESEARCH OF RESIDUAL RESOURCE MODEL DURING MATERIAL DIAGNOSTICS - Mikhalevich, Vladimir; Kraevskiy, Vladimir; Dobranyuk, Yuriy (Scientific Works of Vinnytsia National Technical University, 2015)
There has been analysed and analytically researched the model of a residual resource during two-stage deformation. There had been determined the mathematically admissible changes of parameters α12, n, I12 models which are included in its criterion correlation and with which it acquires only valid values.